Designing the FITRAH Learning Model for Science Education in Elementary Schools - Hamidi, Muhajirin Ramzi, M. Arzani (Journal of Educational Studies, 2025)
The implementation of science education in elementary schools continues to face challenges in promoting active learning, scientific inquiry, and character development, as classroom instruction often remains teacher-centered and focused on content acquisition. This study aimed to develop and analyze the FITRAH Learning Design (Facts, Identification, Experimentation, Reflection, Analysis, and Learning Outcomes), a constructivist and practice-based instructional model designed to enhance science learning in elementary education. The study employed a design-based research (DBR) approach involving expert validation and classroom implementation. Data were collected through expert validation sheets, classroom observations, teacher response questionnaires, student response questionnaires, and field notes, and were analyzed using descriptive statistics and qualitative thematic analysis. The findings revealed that the FITRAH Learning Design achieved a high level of validity and demonstrated strong practicality during classroom implementation. Teachers were able to implement the six instructional stages systematically, while students exhibited greater engagement, active participation in inquiry-based activities, improved science process skills, and more meaningful connections between scientific concepts and everyday life. Teachers also perceived the model as practical and easy to implement, whereas students reported positive learning experiences and high levels of satisfaction. The novelty of this study lies in the development of a comprehensive six-stage instructional framework that integrates constructivist learning principles, inquiry-based science instruction, reflective practice, and character education within a single pedagogical model. Therefore, the FITRAH Learning Design provides both theoretical and practical contributions to the advancement of student-centered science instruction and offers an innovative framework for improving the quality of elementary science education.